POETS AND OTHER ANIMALS: AN INTERVIEW WITH JOHN BURNSIDE. - Dosa, Attila (Scottish Studies Review)
Interviews poet John Burnside, on his poetry. Factors which lead him to writing poetry; Ways in which his poems "Out of Exile" and "Exile's Return" relate to his residence in England and his return to Scotland; Interest in nature; Views on the gap between religious poetry and political poetry.